2022
DOI: 10.34067/kid.0003962021
|View full text |Cite
|
Sign up to set email alerts
|

Is Rechallenge Appropriate in Patients that Develop Immune Checkpoint Inhibitor-Associated AKI?: PRO

Abstract: This is an Early Access article. Please select the PDF button, above, to view it. Be sure to also read the CON: 10.34067/KID.0003902021 and the COMMENTARY 10.34067/KID.0005592021

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…When necessary, it is suggested to switch to H2RAs. This is particularly important when PPI or another AIN-associated drug is used in the setting of rechallenge with ICI therapy [ 95 ].…”
Section: Introductionmentioning
confidence: 99%
“…When necessary, it is suggested to switch to H2RAs. This is particularly important when PPI or another AIN-associated drug is used in the setting of rechallenge with ICI therapy [ 95 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, several retrospective studies including a multicenter study found a relatively low risk of AKI recurring after ICI rechallenge. 5 , 17 , 18 Treatment of ICI-induced sarcoid-like reaction is controversial. Little published scientific information exists regarding rechallenging ICI after immune-related adverse effects, especially after sarcoid-like reactions develop.…”
Section: Discussionmentioning
confidence: 99%
“…In our patient’s case, rechallenging with ICI instead of combination ICI therapy might have been an option, as shown in some cases of ICI-induced AIN. 18 Reinitiating ICI therapy with concurrent low-dose corticosteroid treatment may also be an option for patients with ICI-related sarcoid-like reactions.…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies included only a few patients treated with ICIs. A recent study including 37 patients with ICI-related AKI and 13 with non-ICIrelated AKI found that at the time of AKI diagnosis, the ratio of URBP relative to urine creatinine was significantly higher (median [IQR] 1927[IQR] [1174 vs. 233 [127,989]) in patients with ICIrelated AKI compared to those with the non-ICI-related AKI (22).…”
Section: Urinary Markersmentioning
confidence: 99%